1998
DOI: 10.1007/s001170050333
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia following tumor surgery in the oral cavity and hypopharynx - an analysis by videofluoroscopy

Abstract: Dysphagia is a common complaint following surgical intervention in the oral cavity and hypopharynx, often leading to prolonged postoperative recovery. Videofluoroscopy allows detailed visualization of deglutition, demonstrating the morphology as well as the functional aspects. Therefore, videofluoroscopy provides the basis for further therapeutic management. We discuss the pathology of deglutition in 19 patients recovering from tumor surgery of the oro- and hypopharynx. In most cases the results demonstrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…This is possible using video endoscopy and video fluoroscopy [4,5,9,31,37,38] since both methods allow a classification of the degree of aspiration. We usually use the video endoscopic classification because it can easily be performed with our own equipment (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is possible using video endoscopy and video fluoroscopy [4,5,9,31,37,38] since both methods allow a classification of the degree of aspiration. We usually use the video endoscopic classification because it can easily be performed with our own equipment (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In speech therapy and ENT, tongue movement patterns during swallowing are frequently examined by videofluoroscopy [12,15,16]. According to Watkin ultrasound can also serve this purpose [30].…”
Section: Discussionmentioning
confidence: 99%
“…In der Logopädie, der Phoniatrie und der HNO werden Schluckmuster häufig mit Videofluoroskopie geprüft [12,15,16]. Nach Watkin kann aber auch Ultraschall diesen Zweck erfüllen [30].…”
Section: Discussionunclassified
“…The method provides a score for the severity of the aspiration. 9 In clinical studies, VFSS has been used to investigate dysphagia following surgical intervention in the oral cavity and hypopharynx 10 as well as in patients suffering from severe head injury. 11 A systematic review focusing on studies of adults with acute stroke showed that dysphagia is common and clearly linked to chest infections.…”
Section: Diagnosis Of Dysphagiamentioning
confidence: 99%